Mindful Parenting Behaviors and Emotional Self-Regulation in Children With ADHD and Controls. (12th September 2020) - Evans, Subhadra; Bhide, Sampada; Quek, Jeremey; Nicholson, Jan M; Anderson, Vicki; Hazell, Philip; Mulraney, Melissa; Sciberras, Emma
Abstract: Objective: Mindfulness is defined as paying attention in a particular way: on purpose, in the present moment, and nonjudgmentally and these behaviors can be applied to parenting. Thus far, it is not understood whether mindful parenting (MP) differs in parents of children with and without attention-deficit/hyperactivity disorder (ADHD), and how MP relates to other parenting practices and children's self-regulation. Methods: This study examined the relationships between MP, parenting behaviors and children's self-regulation in 120 families with child ADHD (85% male; mean age = 11.93) and 105 control families (62% male; mean age = 11.98). Parents completed measures of MP (Interpersonal Mindfulness in Parenting Scale), parenting behaviors (parenting warmth, consistency, and anger assessed with the Longitudinal Study of Australian Children measures), psychological distress (Kessler 6), and children's self-regulation (Social Skills Improvement System—self-control subscale). Results: When compared with controls, parents of children with ADHD reported significantly lower MP. Higher MP was associated with lower levels of parent psychological distress, higher levels of parenting warmth and consistency, lower levels of parenting anger, and higher child emotion self-regulation in both groups. In mediation analyses, MP was indirectly associated with child emotion self-regulation through lower parenting anger, with the model accounting for 55% of the variance in child self-regulation. Conclusions: MP is a useful construct for understanding parent behaviors, and children's emotion self-regulation.